2009 IEEE International Conference on Control and Automation 2009
DOI: 10.1109/icca.2009.5410309
|View full text |Cite
|
Sign up to set email alerts
|

Robust control of robot manipulators using dynamic compensator

Abstract: In this paper, a new robust feedback controller for trajectory control of n-link robot manipulators with parametric uncertainties is suggested. The proposed controller using dynamic compensation scheme leads to improvement in transient response while achieving asymptotic regulation in the presence of parametric uncertainties. The ultimate uniform boundedness and asymptotic regulation of the closed-loop system is proved using the Lyapunov method. The performance improvement by the proposed method is demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…The dynamic model presented in [7][8][9][10] is basically the dynamical description of the mechanical arm of the manipulator. Kim and Lee [11] proposed a robust control model of robotic manipulators under parametric uncertainty using only robot link dynamic model based on the Lagrange-Euler equation of motion of robot links. This method of robot dynamic model was used in many research works but recently, it has been criticized in Fateh [12], due to its limitations in feedback application and drawback in its application to the actuator inputs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The dynamic model presented in [7][8][9][10] is basically the dynamical description of the mechanical arm of the manipulator. Kim and Lee [11] proposed a robust control model of robotic manipulators under parametric uncertainty using only robot link dynamic model based on the Lagrange-Euler equation of motion of robot links. This method of robot dynamic model was used in many research works but recently, it has been criticized in Fateh [12], due to its limitations in feedback application and drawback in its application to the actuator inputs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In many situations, the robot dynamics is subject to uncertainties that results from the dynamics parameters uncertainty and called parametric uncertainties, i.e. the precise robot parameters are assumed to be within known bounds [27,28]. There are other sources of uncertainties that are not related to the parameters of the robot dynamics and called nonparametric uncertainties [29] and caused from approximating higher frequency dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…With the use of the robots in critical applications like dealing with hazardous materials and other sensitive applications, the precise control of the robot arms has become an essential requirement. Motivated by such control requirements, for practical and complex control problem of robot manipulators, many research contributions have been reported in the field of robotic control schemes such as proportional-integration-derivative (PID) control, PD control, PI control [2], feedforward compensation control (DFF) [3], adaptive control [4,5], variable structure control [6], computed torque control (CTC) [1,7,8].…”
Section: Introductionmentioning
confidence: 99%